1992
DOI: 10.1021/jo00037a027
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular capture of Pummerer rearrangement intermediates. 3. Interrupted Pummerer rearrangement: capture of tricoordinate sulfur species generated under Pummerer rearrangement conditions

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 1 publication
(1 reference statement)
0
27
0
Order By: Relevance
“…Such an addition is known to occur for sulfoxides, which, in turn, can undergo what is known as Pummerer rearrangement that leads to the elimination of sulfur from the alkyl sulfoxide (43,44). On this basis, we present a mechanism in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such an addition is known to occur for sulfoxides, which, in turn, can undergo what is known as Pummerer rearrangement that leads to the elimination of sulfur from the alkyl sulfoxide (43,44). On this basis, we present a mechanism in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…7b, g) Before our findings, Bates et al had reported that a sulfoxide possessing a highly electron rich pyrrole as the nucleophile exclusively underwent intramolecular sulfenylation, when the side chain of an alkyl aryl sulfoxide was a simple alkyl, 2,8) while the reaction of a sulfoxide whose alkyl side chain contained an electron-withdrawing group on the a-carbon, induced aromatic intramolecular alkylation in an exclusive manner.…”
mentioning
confidence: 53%
“…1) In the interrupted Pummerer reaction, 2) an acylated sulfoxide intermediate (I) undergoes reaction with the nucleophile at the sulfur (sulfenylation), leading to unexpected products under Pummerer reaction conditions.…”
mentioning
confidence: 99%
“…In recent times,s ulfoxides have been employed as precursors to sulfonium salts [2,3] that have been exploited in metal-free C À Hc oupling processes.O nce activated, sulfoxides react with nucleophilic coupling partners at the sulfur atom to afford sulfonium salts,w hich enables the union of avariety of carbon units in asite-selective manner.Incontrast to the transition-metal-mediated reactions described in Sections 3a nd 4, where as toichiometric oxidant is used to regenerate the active metallic species for catalyst turnover, here,the sulfoxide is used as an internal redox-active director and is reduced to the sulfide upon CÀCbond formation. This precludes any further CÀHf unctionalization taking place, ensuring mono-and site-selective C À Cbond formation.…”
Section: à Hc Ouplings Via Sulfonium Intermediates Derived From Sulmentioning
confidence: 99%
“…In aclassical sense,s ulfoxides can direct metalation [1] and undergo Pummerer reactions. [2,3] However,s ulfoxides have recently found aunique place in CÀHbond functionalization owing to their various modes of reactivity,a nd herein, we describe recent advances in this area that shed new light on the utility of sulfoxides.T hese reactions include the use of sulfoxides in transition-metal-catalyzed CÀHactivation, either directed by as ulfoxide in the substrate or by as ulfoxide ligand attached to the metal, and as in situ precursors of sulfonium intermediates that can result in C À Hf unctionalization under metal-free conditions (Scheme 1). These new reactions facilitate expedient access to av ariety of organic scaffolds whereby CÀCb onds,w hich result in the introduction of aryl, heteroaryl, alkenyl, allyl, propargyl, and a-carbonyl motifs,can be constructed at the expense of aC À Hbond with high efficiencya nd site selectivity.…”
Section: Introductionmentioning
confidence: 99%